EKSISTENSI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DALAM MENCEGAH TERBITNYA SERTIPIKAT GANDA DI KANTOR PERTANAHAN SERANG BANTEN - Muhammad Ikhwan; Gunawan Widjaja (JOURNAL OF LAW AND NATION, 2025)
The rise of cases of multiple certificates related to the ownership of land rights. The Government is making efforts to prevent it through the Complete Systematic Land Registration (PTSL) program. The formulation of the problem in writing this journal is 1) what are the legal consequences of having land ownership with multiple certificates? 2) how is the existence of the Complete Systematic Land Registration (PTSL) program in preventing the issuance of multiple certificates at the Serang Banten Land Office? The research method used in this research is literature or library research which is supported by interviews with informants using a qualitative approach. The results of the study show that 1) The legal consequence of having land ownership with multiple certificates is that it does not provide legal certainty, because the purpose of a person doing land registration is to obtain a certificate as a perfect means of proof. But with the emergence of multiple certificates, it creates legal uncertainty in terms of land registration. Apart from that, there are other legal consequences, namely the emergence of losses, meaning that a person expects to obtain legal status for his land, but due to multiple certificates and then being declared lost in court with the consequence in the form of a certificate being declared null and void, the person automatically suffers a loss. 2) The existence of the Complete Systematic Land Registration (PTSL) program in preventing the issuance of multiple certificates at the Serang Banten Land Office, namely this program is one of the programs created to reduce land disputes such as multiple certificate disputes. The role of the Complete Systematic Land Registration Program based on facts can reduce the occurrence of land disputes.